Marta : a novel - Orzeszkowa, Eliza, 1842-1910 (Ohio University press Polish and Polish-American studies series, 2018)
Of trailblazing Polish novelist Eliza Orzeszkowa's many works of social realism, Marta is among the best known, but until now it has not been available in English. Easily a peer of The Awakening and A Doll's House, the novel was well ahead of English literature of its time in attacking the ways the labor market failed women.